PENGARUH PROFITABILITAS, STRUKTUR MODAL, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Ridha Asmara Oktaviana; Rosita Rosita (ITB AAS Indonesia Surakarta, 2023)
This study aims to examine the effect of profitability, capital structure, and dividend policy on company value during the COVID-19 pandemic in Indonesia. The independent variables in this investigation are profitability (ROA), capital structure (DER), and dividend policy (DPR), with the dependent variable firm value (PBV). The sample used in this study is 19 manufacturing companies in the Consumer Goods sector from 2018 to 2021 which are listed on Indonesia Stock Exchange using the purposive sampling method. The method used in this study is quantitative method with multiple linear regression data analysis techniques. The results showed that profitability had a positive and significant effect on firm value, capital structure and dividend policy had no effect on firm value. Keywords : profitability, capital structure, dividend policy, and firm value.